Smoothing by Convex Quadratic Programming (Journal of Computational Mathematics, 2005)
In this paper, we study the relaxed smoothing problems with general closed convex constraints. It is pointed out that such problems can be converted to a convex quadratic minimization problem for which there are good programs in software libraries.
Keywords: Relaxed smoothing; Convex quadratic programming.